Ciri-Ciri Gereja Yang Sejati Menurut Pandangan Orang Kristen - Marlince Diana Lende; Ronaully Marbun (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This abstract discusses the characteristics of the true church according to Christian views, emphasizing the importance of faithfulness to the Word of God as the primary foundation. The true church is a community that faithfully proclaims the Gospel of Christ purely, without addition or subtraction from the teachings of the Bible. This faithfulness serves as the basis for the church’s existence as the living body of Christ, functioning to spread salvation to all people. Besides faithfulness to the Word, the proper administration of the sacraments is also an important characteristic of the true church. Sacraments such as baptism and the Lord’s Supper are conducted according to Christ’s commands and serve as means of grace that strengthen the faith of the congregation. The spiritual discipline practiced within the church maintains the holiness of the members and encourages repentance and restoration, so that the community continues to live in truth and love. Unity and holiness reflect the church’s calling to live in love and truth, while the apostolic nature shows its adherence to the teachings of the apostles. Catholicity affirms that the true church is universal and transcends cultural and geographical boundaries.